Pathogenic potential of ornithogenic Escherichia coli strains detected in the Earth's polar regions - Batyrbek I. Aslanov; Daniil V. Azarov; Maria A. Makarova; Elizaveta G. Marysheva; Lyudmila A. Kraeva; Aleksey S. Mokhov; Ekaterina A. Lebedeva; Nikita E. Goncharov; Natalya V. Lebedeva; Dmitry A. Starikov; Victoria V. Kolodzhieva; Dmitry E. Polev; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Pathogenic strains of Escherichia coli are an important object of surveillance within the One Health concept in the wild, agriculture and human society.